The psychological discourse of existential conflict in the novel by Honore de Balzac «Gobsec» (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article deals with the psychological aspects of thephenomenon of existential conflict in the worldview content of a new typeof personality. The essence of existential conflict in the story of Honorede Balzac «Gobsheck» is outlined, the psychological characteristics ofthe confrontation between man and society are explained, which causesalienation of the person from the world and from himself. The essence ofartistic psychologism in literary works is determined. The author presentsthe results of empirical study of typical models of conflicting behaviorof young schoolchildren. The problem of development of constructiveworldview of schoolchildren in the educational system, and in particular inthe study of literature, is emphasized. The problem of organizing the workof a teacher with students in foreign literature lessons is considered.
Keywords: existentiality; conflict; psychologism; cognitive activity; worldview